Optimal Scheduling of Source-Load Complementation Based on Green Certificate-Step Carbon Trading Interaction - Yuxiang MENG; Gang MA; Hao LI; Weikang LI; Jianwei XU; Tianyu LI (Zhongguo dianli)
Aiming at the low-carbon economic operation of regional integrated energy systems (RIES) coupled with multi-energy, a source-load complementary optimal scheduling model is proposed based on green certificate-step carbon trading interaction. Firstly, a green certificate-step carbon trading interactive mechanism is introduced to improve the consumption level of source-side renewable energy and reduce system carbon emissions. Secondly, the incentive-based demand response and peak-shaving benefits with consideration of user satisfaction are introduced on the load side to realize “peak-shaving and valley-filling” of thermoelectric loads. Finally, with the goal of minimizing the running cost of RIES, the model is solved using the Cplex toolbox. The results of the case study show that the green certificate-step carbon trading interactive mechanism is helpful to give full play to the optimization ability of incentive demand response, realize the coordinated reduction of carbon at the source and load side, reduce the system operation cost, and effectively improve the green, low-carbon and economic operation of the system.